60*(24.95*.6)+3+(59*.75)=

Simple and best practice solution for 60*(24.95*.6)+3+(59*.75)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 60*(24.95*.6)+3+(59*.75)= equation:


Simplifying
60(24.95 * 0.6) + 3 + (59 * 0.75) = 0

Multiply 24.95 * 0.6
60(14.97) + 3 + (59 * 0.75) = 0

Multiply 60 * 14.97
898.2 + 3 + (59 * 0.75) = 0

Multiply 59 * 0.75
898.2 + 3 + (44.25) = 0
898.2 + 3 + 44.25 = 0

Combine like terms: 898.2 + 3 = 901.2
901.2 + 44.25 = 0

Combine like terms: 901.2 + 44.25 = 945.45
945.45 = 0

Solving
945.45 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 3x+x-5=x-3 | | 98=7*a+b*28 | | x-4(x+30)=24 | | 2n-10=x+20 | | 3(5x-2)+4(17-2x)-2(3x+1)=-1 | | 13x+17-4x=24 | | 19-2x-3=2x+3+x | | 2(x+1)=8(x-3)-10 | | 4y-3x-8=0 | | 8.3=4.1+10.5 | | 4y-6(y+4)=1-y | | 21a+21=28a+14 | | 5sinx-8cosx=6 | | 4(-5+x)=5x+.5 | | 2x^2+4x+4=20 | | .66666666666666(4x-5)=8 | | 18-(5m+8)=5+4m-13 | | 3x-5=7x+2-3 | | (4x-5)+(2x+20)=45 | | 6x+x-0.9=6x+0.9 | | -3-6X=28 | | X+65X+1000=0 | | (18)-2y-4= | | 3/4x+2-5/4=-6 | | 13=2f-5 | | 6x+3-8x-16=0 | | 5x+7=-7x+43 | | 9t=4 | | -2(3x+1)-10=4 | | 5x+3=33-x | | 1/4x+4=-6 | | 2-x=-2x-12 |

Equations solver categories